2010
DOI: 10.1177/0300985810381910
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Response to Therapeutic Gold Bead Implantation in Canine Hip Joint Osteoarthritis

Abstract: Inflammatory changes associated with periarticular pure gold bead implants were studied in dogs involved in a clinical trial investigating motor dysfunction and chronic pain owing to hip joint dysplasia and osteoarthritis. Gold beads were percutaneously implanted via a needle into different locations surrounding the greater trochanter of the femur. Nine dogs with implants were necropsied. In all examined animals, characteristic histologic lesions were observed in the tissue surrounding the gold implants-namely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 27 publications
2
8
0
2
Order By: Relevance
“…Our results show that acupuncture points represent a potential administration route for stem cells. A long-term study involving 73 dogs with hip OA showed the efficacy of gold bead implantation inserted through needles at acupuncture points as a pain-relieving treatment and improved mobility [30]. This study supports the use of acupuncture for the treatment of HD and OA.…”
Section: Discussionsupporting
confidence: 60%
“…Our results show that acupuncture points represent a potential administration route for stem cells. A long-term study involving 73 dogs with hip OA showed the efficacy of gold bead implantation inserted through needles at acupuncture points as a pain-relieving treatment and improved mobility [30]. This study supports the use of acupuncture for the treatment of HD and OA.…”
Section: Discussionsupporting
confidence: 60%
“…A cytotoxin molecule NN-32, isolated from Naja naja venom has also been reported to possess anti-arthritic property8. Gold has been reported as a therapeutic agent against arthritis in traditional medicine systems of India910. Research in the area of nanotechnology revealed that gold nanoparticles had anti-inflammatory property and could be used for the treatment of arthritis11.…”
mentioning
confidence: 99%
“…The Au(CN)2 − action is to destroy the inflammatory cells around the joint that are contributing to joint inflammation (Lie et al . ). The use of gold implants to treat canine hip dysplasia has been reported.…”
Section: Gold Implantmentioning
confidence: 97%
“…The negative charge is neutralised by Au3 + that binds with thiolate and thioether ligands on protein, neutralising the negative charge. The Au (CN)2 À action is to destroy the inflammatory cells around the joint that are contributing to joint inflammation (Lie et al 2011). The use of gold implants to treat canine hip dysplasia has been reported.…”
Section: Gold Implantmentioning
confidence: 99%